Impact of early childhood educators’ pedagogical content knowledge on early graders academic success in the Sissala East Municipal - Mahamud, Wasila (Research Journal in Advanced Social Sciences, 2021)
The study examined the impact of early childhood educators’ pedagogical content knowledge on early graders academic success in the Sissala East Municipal. The target population for the research included all early childhood educators in the Sissala East Municipal in the Upper West Region of Ghana. This research employed multiple sampling techniques, which include: purposive, simple random, criterion sampling and lottery sampling techniques. The researcher selected all early childhood educators using purposive sampling. The total sample for the study was 164 early childhood educators. Self-developed questionnaire, interview guides and observation checklist were used for data collection. The quantitative data analysis was done using the Statistical Package for Social Sciences (SPSS) software version 20. The study revealed that majority of the respondents agreed that the pedagogical content knowledge of teachers and teachers’ teaching-learning strategies significantly enhanced the performance of students. It is concluded that pedagogical content knowledge of teachers has an impact on learners’ performance. The findings of this study will guide teacher preparation trainers and curriculum designers to correlate their relayed curriculum on how Language and literacy practices are and the extent of their implementation in the classrooms.